2013
DOI: 10.1111/1348-0421.12090
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of antimicrobial‐resistant lactic acid bacteria in natural cheese in Japan

Abstract: To determine and compare the extent of contamination caused by antimicrobial-resistant lactic acid bacteria (LAB) in imported and domestic natural cheeses on the Japanese market, LAB were isolated using deMan, Rogosa and Sharpe (MRS) agar and MRS agar supplemented with six antimicrobials. From 38 imported and 24 Japanese cheeses, 409 LAB isolates were obtained and their antimicrobial resistance was tested. The percentage of LAB resistant to dihydrostreptomycin, erythromycin, and/or oxytetracycline isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
1
8
1
Order By: Relevance
“…Moderate level of erythromycin (63/105, 60%) and tetracycline resistance (38/105, 36.19%) reported in present study is in agreement with many of the previous studies (Lonkar et al, 2005;Egervärn et al, 2009;Karapetkov et al, 2011;Ishihara et al, 2013;Dec et al, 2015Dec et al, , 2017 Erythromycin resistance is generally encoded by erm(A), erm(B) and erm(C) while resistance to tetracycline by tet(M), tet(K), tet(S), tet(L) and tet(O) (Egervärn et al, 2009;Dec et al, 2015Dec et al, , 2017. Resistance genes including erm(A), erm(B), erm(C), tet(M), tet(K), tet(S) and tet (O) have been detected from lactobacilli isolated from poultry gut, fermented foods and human gut in previous studies from different parts of the world (Karapetkov et al, 2011;Nawaz et al, 2011;Ishihara et al, 2013;Carrique-Mas et al, 2015;Dec et al, 2015Dec et al, , 2017van Schaik, 2015;). Although, erm(B) or tet(M) have also been successfully amplified from pathogenic bacteria (Farid et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Moderate level of erythromycin (63/105, 60%) and tetracycline resistance (38/105, 36.19%) reported in present study is in agreement with many of the previous studies (Lonkar et al, 2005;Egervärn et al, 2009;Karapetkov et al, 2011;Ishihara et al, 2013;Dec et al, 2015Dec et al, , 2017 Erythromycin resistance is generally encoded by erm(A), erm(B) and erm(C) while resistance to tetracycline by tet(M), tet(K), tet(S), tet(L) and tet(O) (Egervärn et al, 2009;Dec et al, 2015Dec et al, , 2017. Resistance genes including erm(A), erm(B), erm(C), tet(M), tet(K), tet(S) and tet (O) have been detected from lactobacilli isolated from poultry gut, fermented foods and human gut in previous studies from different parts of the world (Karapetkov et al, 2011;Nawaz et al, 2011;Ishihara et al, 2013;Carrique-Mas et al, 2015;Dec et al, 2015Dec et al, , 2017van Schaik, 2015;). Although, erm(B) or tet(M) have also been successfully amplified from pathogenic bacteria (Farid et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…The percentage of enrofloxacin-resistant Lactobacillus strains (MIC≥64 μg/ml) in the turkeys (60%) was higher than in chickens (48%) and in geese (23%) in Poland [ 16 , 45 ]. Lactobacilli from other sources, such as dairy products or cattle intestine, are usually sensitive to enrofloxacin [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have reported greater susceptibility of LAB to enrofloxacin. The MIC range noted by Ishihara et al [ 54 ] for lactobacilli isolated from dairy products was 1–8 μg/ml, and in the case of bovine lactobacilli MIC ≥64 μg/ml was noted for only 3% of isolates [ 44 ]. The presence of low MIC values for enrofloxacin, i.e.…”
Section: Discussionmentioning
confidence: 99%